A Novel Extracellular Calcium Sensing Mechanism in Voltage-Gated Potassium Ion Channels - Johnson, J. P. (J Neurosci, 2001)
Potassium (K(+)) channels influence neurotransmitter release, burst firing rate activity, pacing, and critical dampening of neuronal circuits. Internal and external factors that further modify K(+) channel function permit fine-tuning of neuronal circuits. Humanether-à-go-go-related gene (HERG) K(+) channels are unusually sensitive to external calcium concentration ([Ca(2+)](o)). Small changes in [Ca(2+)](o) shift the voltage dependence of channel activation to more positive membrane potentials, an effect that cannot be explained by nonspecific surface charge screening or channel pore block. The HERG–calcium concentration–response relationship spans the physiological range for [Ca(2+)](o). The modulatory actions of calcium are attributable to differences in the Ca(2+)affinity between rested and activated channels. Adjacent extracellular, negatively charged amino acids (E518 and E519) near the S4 voltage sensor influence both channel gating and Ca(2+)dependence. Neutralization of these charges had distinct effects on channel gating and calcium sensitivity. A change in the degree of energetic coupling between these amino acids on transition from closed to activated channel states reveals movement in this region during channel gating and defines a molecular mechanism for protein state-dependent ligand interactions. The results suggest a novel extracellular [Ca(2+)](o) sensing mechanism coupled to allosteric changes in channel gating and a mechanism for fine-tuning cell repolarization.